Spatio-temporal spike dynamics predict surgical outcome in adult focal epilepsy. (February 2022) - Klimes, Petr; Peter-Derex, Laure; Hall, Jeff; Dubeau, François; Frauscher, Birgit
Highlights: Analysis of spike dynamics shows that epilepsy surgery outcome depends on strong, single and stable sources. Spatio-temporal spike dynamics is an objective and easy-to-apply marker for epilepsy surgery outcome prediction. The best results for outcome prediction were achieved by 18-h periods or longer. Abstract: Objective: We hypothesized that spatio-temporal dynamics of interictal spikes reflect the extent and stability of epileptic sources and determine surgical outcome. Methods: We studied 30 consecutive patients (14 good outcome). Spikes were detected in prolonged stereo-electroencephalography recordings. We quantified the spatio-temporal dynamics of spikes using the variance of the spike rate, line length and skewness of the spike distribution, and related these features to outcome. We built a logistic regression model, and compared its performance to traditional markers. Results: Good outcome patients had more dominant and stable sources than poor outcome patients as expressed by a higher variance of spike rates, a lower variance of line length, and a lower variance of positive skewness (ps < 0.05). The outcome was correctly predicted in 80% of patients. This was better or non-inferior to predictions based on a focal lesion ( p  = 0.016), focal seizure-onset zone, or complete resection (ps > 0.05). In the five patients where traditional markers failed, spike distribution predicted the outcome correctly. The best results were achieved by 18-h periods or longer. Conclusions: Analysis of spike dynamics shows that surgery outcome depends on strong, single and stable sources. Significance: Our quantitative method has the potential to be a reliable predictor of surgical outcome.